Tunneling nanotubes spread fibrillar α‐synuclein by intercellular trafficking of lysosomes. (22nd August 2016) - Abounit, Saïda; Bousset, Luc; Loria, Frida; Zhu, Seng; de Chaumont, Fabrice; Pieri, Laura; Olivo‐Marin, Jean‐Christophe; Melki, Ronald; Zurzolo, Chiara
Abstract: Synucleinopathies such as Parkinson's disease are characterized by the pathological deposition of misfolded α‐synuclein aggregates into inclusions throughout the central and peripheral nervous system. Mounting evidence suggests that intercellular propagation of α‐synuclein aggregates may contribute to the neuropathology; however, the mechanism by which spread occurs is not fully understood. By using quantitative fluorescence microscopy with co‐cultured neurons, here we show that α‐synuclein fibrils efficiently transfer from donor to acceptor cells through tunneling nanotubes (TNTs) inside lysosomal vesicles. Following transfer through TNTs, α‐synuclein fibrils are able to seed soluble α‐synuclein aggregation in the cytosol of acceptor cells. We propose that donor cells overloaded with α‐synuclein aggregates in lysosomes dispose of this material by hijacking TNT‐mediated intercellular trafficking. Our findings thus reveal a possible novel role of TNTs and lysosomes in the progression of synucleinopathies. Synopsis: Misfolded α‐synuclein fibrils propagate in cell culture by transferring between neurons through tunneling nanotubes (TNTs) inside lysosomes, indicating a possible role of TNTs and lysosomes in the spreading and propagation of Parkinson's pathology. α‐synuclein fibrils are targeted to cell lysosomes for degradation. α‐synuclein fibrils enhance formation of TNTs between neighbouring cells, possibly though increasing oxidative stress. Lysosomes overloaded with α‐synuclein fibrils transfer from donor cells to neighbouring (acceptor) cells inside TNTs connecting the two populations. Once in acceptor cells, α‐synuclein fibrils are able to seed the aggregation of endogenous soluble cytosolic α‐synuclein, conceivably by escaping lysosomes. Abstract : Lysosomes containing α‐synuclein fibrils can transfer between primary neurons via tunneling nanotubes.